PENGARUH PENGGUNAAN MEDIA PUZZLE PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 3 PONTIANAK PENGARUH MODEL PEMBELAJARAAN KOOPERATIF TIPE - Novi Septiana; Budiman Tampubolon; Ludovicus Maditya Hari Christanto (Universitas Tanjungpura, 2021)
AbstractThis research aims to determine effect of media puzzle learning media on learning outcomes in learning geography in class XI IPS Senior High School 3 Pontianak. The Research Method is an experimental method in the form of a Quasi Experimental Design Research with a Nonquivalent Control Group Design. The research population was all students of class XI IPS Senior High School 3 Pontianak with a sample of 2 class. The sampling technique is purposive sampling. Research instruments in the form of a final test in the form of multiple choice questions amounted to 50. The final test calculation results obtained average of 63.59 experimental class and an average of 73.87 control class with a tcount of 4.172 and a table of 1.999. Through on tcount> ttable, means Ha is rejected then,there is differences in student learning outcomes in geography learning that applies the learning with media puzzle those that apply the group discussion learning method in class XI IPS Senior High School 03 Pontianak. Based on the results of the calculation of the effect size obtained d value of 0.96. This proves that media learning has a high influence on student learning outcomes in class XI IPS of Senior High School 3 Pontianak.Keyword: Learning with Media Puzzle, Learning Outcomes, Media Learning Geography